RHODODENDRON PSEUDOMADDENII (ERICACEAE), A NEW SPECIES FROM INDIA - Mao, A. A.; Bhaumik, M. (Edinburgh Journal of Botany, 2015)
A new species, Rhododendron pseudomaddenii A.A.Mao & M.Bhaumik (Ericaceae), is described and illustrated from India.
Keywords: Ericaceae; India; new species; Rhododendron